Students’ Reflection on Pair-work Information Gap (PIG) Activity in an EFL Instructional Context - Wa Ode Zulhidjah Awalyah; Abdul Halim; Dewi Atikah (IAIN KENDARI, 2020)
This qualitative research aims to investigate the students' response to pairwork information gap (PIG) activity in an EFL classroom. Reflective accounts of eighteen senior high school students were analyzed. The findings of this study indicated that the students enjoyed the classroom activities under PIG technique. The students revealed their enthusiasm, happiness, and enjoyment in learning English. They also acknowledge that activities under PIG could foster them to study and follow the lesson more dynamically. This present study implies that the use of PIG activity in the classroom should involve a variety of activities to raise students’ participation in the learning process. Keywords: EFL classroom; pairwork information gap; reflective account; senior high school; students' response